Effect of different doses of atorvastatin on hs-CRP of NSTEMI patients before and after PCI - Wen Liu (Journal of Hainan Medical University, 2016)
Objective: To discuss the effect of different doses of atorvastatin on hs-CRP of non ST elevation acute myocardial infarction (NSTEMI) patients before and after PCI. Methods: A total of 120 cases with NSTEMI who were admitted in our hospital from February 2013 to February 2014 were selected and were divided into low-dose group and high-dose group based on different doses of atorvastatin. hs-CRP levels and related index changes were observed before and after PCI treatment. Results: Before treatment,serum hs-CRP levels, IL-6 levels in both groups had no significant difference (P>0.05); 24 h after treatment, serum hs-CRP levels, IL-6 levels in both groups were increased; 2 weeks after treatment, serum hs-CRP levels, IL-6 levels in high-dose group were significantly decreased than before treatment, while 4 weeks after treatment, serum hs-CRP levels, IL-6 levels in low-dose group were significantly decreased than before treatment. Compared with before treatment, difference was significant (P<0.05); after treatment, cTNI and CK-MB levels in both groups were significantly increased, however, cTNI and CK-MB levels in high-dose group were much lower than that in lowdose group (P<0.05); adverse cardiac event occurrence rate in high-dose group was lower than that in low-dose group (P<0.05).Conclusions: High-dose of atorvastatin treatment could significantly improve PCI-caused inflammation and myocardial damages before and after PCI treatment for NSTEMI patients, which was deserved promotional value.